PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ADOBE FLASH UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN AKUNTANSI DI SMK - Wulandari, Lintang; ., Sudiyanto; ., Sohidin (Tata Arta : Jurnal Pendidikan Akuntansi, 2017)
ABSTRACTThe objectives of this research are to investigate (1) the feasibility of Adobe Flash-based learning media in accounting learning at State Vocational High School, and (2) the effectiveness of Adobe Flash-based learning media to improve the students learning motivation in accounting at State Vocational High School. This research used the research and development (R&D) method. The validation of the product design was done by a learning media expert, a learning material expert, and a practitioner. The subjects of the product testing included 10 students at the preliminary product testing, 30 students in Grade XI Accounting 2 (experimental class) and 30 students in Grade XI Accounting 1(control class) of Sejati Vo-cational High School at the main extended-field testing. The data of research were collected through a questionnaire and documentation. The data were analyzed by using the descriptive analysis and the infer-ential analysis. The results of the research are as follows. Firstly, the developed Adobe Flash-based learn-ing media is feasible to be used in Accounting learning at State Vocational High School. Itâs proven of me-dia feasibility assessment average by a learning media expert which received score of 4.833, and was cat-egorized âvery feasibleâ, assessment of learning material expert which received score of 3.74, and was categorized âfeasibleâ, assessment of practitioner which received score of 4.19, and was categorized âfeasibleâ, and assessment of students which received score of 4.324, and was categorized âvery feasi-bleâ. Secondly, the developed Adobe Flash-based learning media in Accounting is effective to improve the students learning motivation at State Vocational High School. The research shown the difference of learn-ing motivation between the experimental class and the class control with the significance value of 0.000 which was smaller than 0.05, the average scores of learning motivation of experimental class is 4.05 and the control class is 3.61 belong to âhigh" categories. Thus, the developed of Adobe Flash-based learning media is feasible and effective in improving the students learning motivation in accounting at State Voca-tional High School.Keywords:Learning Media, Adobe Flash, Learning Motivation.ABSTRAKPenelitian ini bertujuan mengetahui: (1) kelayakan media pembelajaran berbasis Adobe Flash un-tuk pembelajaran akuntansi di SMK, dan (2) keefektifan media pembelajaran berbasis Adobe Flash dalam meningkatkan motivasi belajar siswa pada pembelajaran Akuntansi di SMK. Penelitian ini merupakan penelitian pengembangan atau Research and Development (R&D). Validasi desain dilakukan oleh ahli media, ahli materi, dan praktisi. Subjek uji coba terdiri dari 10 siswa pada uji coba awal, serta 30 siswa pada kelas XI Akuntansi 2 (kelas eksperimen) dan 30 siswa pada kelas XI akuntansi 1 (kelas kontrol) di SMK Sejati* pada uji coba lapangan. Instrumen pengumpulan data terdiri dari angket dan dokumentasi. Teknik analisis data yang digunakan pada penelitian ini adalah analisis statistik deskriptif dan analisis in-ferensial. Hasil penelitian menunjukkan bahwa, Pertama, media pembelajaran berbasis Adobe Flashdinya-takan layak digunakan pada pembelajaran akuntansi di SMK. Hal ini dibuktikan dengan hasil rata-rata val-idasi dari ahli media sebesar 4,833 dengan kategori âsangat layak, ahli materi sebesar 3,74 dengan kate-gori âlayakâ, praktisi sebesar 4,19 dengan kategori âlayakâ, serta penilaian siswa sebesar 4,324 dengan kategori âsangat layakâ. Kedua, media pembelajaran berbasis Adobe Flash pada pembelajaran Akuntansi efektif meningkatkan motivasi belajar siswa di SMK. Temuan menunjukkan adanya perbedaan motivasi belajar siswa antara kelas eksperimen dan kelas kontrol dengan perolehan signifikansi 0,000 atau kurang dari 0,05, dengan rata-rata motivasi belajar siswa pada kelas eksperimen 4,05 dan kelas kontrol 3,61 dalam kategori âtinggiâ. Simpulan penelitian ini adalah pengembangan media pembelajaran berbasis adobe flash layak dan efektif dalam meningkatkan motivasi belajar siswa pada pembelajaran akuntansi di SMK.Kata Kunci :Media Pembelajaran, Adobe Flash, Motivasi Belajar.